Replikasi SIPBM, Pembentukan Pospaud, dan Peningkatan Mutu Dokter Kecil di Desa Cigadung dan Parereja Kecamatan Banjarharjo Kabupaten Brebes - Isti Hidayah; Lita Latiana; Widowati Widowati; Tatirah Tatirah (Journal of Dedicators Community, 2019)
The target of the Partnership Program's activities is Parereja and Cigadung village, district of Banjarharjo, Brebes regency. Priority issues that be the focus on this partnership program are: (1) Quite a lot of early childhood have not served yet in PAUD; (2) There are school-aged children in primary education level not going to school; (3) The high number of stunting and maternal mortality rate (4) The lack of awareness about nutrition of pregnant women and toddlers; (5) The lack of health services for children in school. The target that has been achieved are: (1) The availability of community-based education data in 2018 as a reference for organizing Cigadung village program in the next year; (2) Formed a POSPAUD model in Parereja; (3) formed PKBM in Parereja; (4) The availability of the health equipment and skills of the UKS and little doctor in Cigadung 01 and Parereja 01 elementary school. The methods that used in this program are the empowerment of the Community (community-based), training approaches, demonstrations, simulations, and practice with assistance. In addition, followed by strengthening community-based human resources who collaborate-participatively with Baperlitbangda and local college to ensure the quality and sustainability of the program